COMPARATIVE NUTRITIONAL AND MINERAL ANALYSIS OF FERMENTED PENTACLETHRA MACROPHYLLA (UKPAKA), FERMENTED RICINUS COMMUNIS (OGIRI), AND FERMENTED PROSOPIS AFRICANA SEED (OKPEYE) - AGBO, NDIDIAMAKA. JUSTINA (FUDMA JOURNAL OF SCIENCES, 2024)
Fermented African mesquite bean, Castor oil bean, and African oil bean seeds were Purchased at Ogige Main Market in Nsukka Local Government of Enugu State and examined for the relative assessments of their mineral and nutritional proximate qualities. The Association of Official Agricultural Chemists’ techniques were used to ascertain the approximate composition and mineral characteristics of the fermented samples. The fermented African oil bean seed had the highest lipid content (43.31%) and fibre (16.85%), whereas the fermented African mesquite bean had the highest levels of carbs (41.98%), ash (6.54%), and protein (33.64%). The beans with fermented castor oil showed the highest moisture content (29.4320%). Fermented African mesquite bean seed had the highest levels of calcium (1813.30 mg/L), magnesium (292.03 mg/L), and iron (48.26 mg/L), according to the mineral contents, whereas fermented castor bean seed had the highest potassium levels (3,544.72 mg/L). There were no heavy metals such as lead(Pb), chromium (Cr), cadium (Cd), or cobalt (Co) in any of the samples. In comparison to fermented African oil bean and Castor oil bean seeds, it can be stated that fermented African mesquite bean seeds (Okpeye) contain higher amounts of protein, carbohydrates, and ash.